Durability assessment of vacuum-infused GFRP laminates and I-beams in marine environments - Xinqiang Xi; Shaojie Zhang; Zhi-hao Hao; Peng Feng; Fei Zhao (Case Studies in Construction Materials)
This study investigates the long-term durability of vacuum-infused glass fiber-reinforced polymer composite (GFRP) laminates and I-beams in marine environments. Through an extensive experimental program, material-level (laminates) and component-level (I-beams) specimens were subjected to three distinct aging conditions: natural offshore exposure; standard simulated marine environment (UV radiation with seawater immersion at room temperature), and accelerated aging condition (UV radiation with seawater immersion at 60°C). Tensile and compressive tests on laminates at different fiber orientations were conducted to evaluate anisotropic degradation, while flexural tests on I-beams evaluated component degradation. Microstructural characterization further revealed degradation mechanisms. In addition, a fluorocarbon coating was tested for its protective effectiveness. Key findings reveal that laminates and I-beams exhibited similar degradation trends under natural and standard environments, validating the reliability of laboratory simulations. While accelerated aging induced more severe degradation, failure mechanisms remained consistent. Laminates experienced greater strength degradation in tension (over 30 %) and compression (around 10 %) compared to the flexural strength degradation of I-beams (8.64 %) under the same conditions. Furthermore, the fluorocarbon coating effectively mitigated degradation, although its effectiveness declined at elevated temperature. This study enhances the understanding of GFRP durability in marine environments by correlating laboratory simulations with natural exposure, offering valuable insights for marine applications of vacuum-infused GFRP structures.